Marty supreme [videorecording (Blu-Ray)] - Lopatin, Daniel (A24, 2026)
"Marty Mauser, a silver-tongued hustler with a dream that no one respects: to become the world champion table tennis player. Hopping from one scheme to the next, Marty goes to hell and back in pursuit of greatness, journeying from the Lower East Side to London, Paris, Tokyo, the Great Pyramids, and back with a trail of scorned lovers, business moguls, and mobsters hot on his tail."--